Prevalence and predicting factors for anxiety in Thai women with abnormal cervical cytology undergoing colposcopy - Jerachotechueantaveechai,T. (Asian Pacific Organization for Cancer Prevention, 2015)
Aim: To compare prevalence of anxiety in women with abnormal cervical cytology (Pap) undergoing colposcopy to that of women attending the outpatient clinic for check-up and to examine predicting factors. Materials and Methods: In this cross-sectional analytical study, 100 women with abnormal cervical cytology (abnormal Pap group) and 100 women who attended our outpatient clinic for check-up (control group) were recruited from June 2013 to January 2014. The Hospital Anxiety and Depression Scale (HADS) was employed to determine anxiety in the participants with the score of = 11 suggestive of clinically significant anxiety. The prevalence of anxiety and the mean HADS scores for anxiety were compared between the groups. For those with abnormal Pap, association between clinical factors and anxiety was assessed. A p-value of < 0.05 was considered significant. Results: Median age was different between the groups, 44.0 years in the abnormal Pap group and 50.0 years in the control group (p=0.01). The proportion of participants who had more than one sexual partner was higher in the abnormal Pap group, 39.2% vs. 24.7% (p=0.03) and the prevalence of anxiety was significantly higher 14/100 (14.0%) vs. 3/100 (3.0%) (p < 0.01). The prevalence of depression was comparable between the groups. The mean HADS scores for anxiety and depression subscales were significantly higher in the abnormal Pap group, 6.6 vs. 4.8 (P < 0.01) and 3.9 vs. 3.1 (p=0.05), respectively. For the abnormal Pap group, no definite association between clinical factors and anxiety was demonstrated. Conclusions: The prevalence of anxiety in women with abnormal Pap awaiting colposcopy was significantly higher than that of normal controls. Special attention including thorough counselling, with use of information leaflets and psychological support, should be directed to these women.